Asymmetric global network connectivities in the world city network, 2013. (February 2017) - Yang, Xiaolan; Derudder, Ben; Taylor, Peter J.; Ni, Pengfei; Shen, Wei
Abstract: This paper builds upon world city network studies using the interlocking network model to introduce an additional way of measuring inter-city connectivity. Using firms' service values for cities to indicate directions of potential workflows, a new measure of asymmetric network connectivity is specified to include uneven power relations in the analysis. This is then employed in analyses of the latest service values matrix (175 firms × 526 cities) for 2013. Two types of analyses are performed. First, the aggregate measures of asymmetric network connectivity are computed and compared to the conventional measure of global network connectivity. Results show an accentuation of the hierarchical tendencies in the world city network. Second, the asymmetric connectivity is disaggregated into its three components - dominant, equivalence and subordinate - to produce a set of further measures. Results tend to distinguish dominant 'global places', often financial centres, from places where firms 'have to be', largely capital cities of medium-sized states. Highlights: We extend research on world city networks by specifying a measure of asymmetric network connectivity Using 2013 data, this measure is computed and compared to the conventional measure of global network connectivity Asymmetric connectivity is disaggregated into its three components: dominant, equivalence and subordinate Results tend to distinguish dominant 'global places'from places where firms 'have to be' Results are used to interpret the uneven integration of Chinese in the world city network